A Real-Business-Cycle model with an informal sector: Lessons for Bulgaria (1999-2018) - VASILEV, Aleksandar (Journal of Mathematical Economics and Finance; Vol 10 No 1 (2024): JMEF, Volume X, Issue 1(18), Summer 2024, 2024)
We introduce an informal sector into a real-business-cycle setup augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of the presence of a grey economy for the cyclical fluctuations in Bulgaria. We find that incorporating an informal sector improves the model fit against data, as compared to the standard RBC model, and thus this sector is an important ingredient that needs to be considered by researchers interested in business cycle-, or public finance issues.